Global status of diabetes prevention and prospects for action: A consensus statement. Issue 6 (8th June 2018) - Ibrahim, Mahmoud; Tuomilehto, Jaakko; Aschner, Pablo; Beseler, Lucille; Cahn, Avivit; Eckel, Robert H.; Fischl, Amy Hess; Guthrie, George; Hill, James O.; Kumwenda, Mick; Leslie, R. David; Olson, Darin E.; et al.
Summary: Primary prevention of type 2 diabetes (T2D) should be achievable through the implementation of early and sustainable measures. Several randomized control studies that found success in preventing the progression to T2D in high‐risk populations have identified early and intensive intervention based on an individualized prevention model as the key factor for participant benefit. The global prevalence of both overweight and obesity has now been widely recognized as the major epidemic of the 21st century. Obesity is a major risk factor for the progression from normal glucose tolerance to prediabetes and then to T2D. However, not all obese individuals will develop prediabetes or progress to diabetes. Intensive, multicomponent behavioural interventions for overweight and obese adults can lead to weight loss. Diabetes medications, including metformin, GLP‐1 agonists, glitazones, and acarbose, can be considered for selected high‐risk patients with prediabetes when lifestyle‐based programmes are proven unsuccessful. Nutrition education is the cornerstone of a healthy lifestyle. Also, physical activity is an integral part of the prediabetes management plan and one of the main pillars in the prevention of diabetes. Mobile phones, used extensively worldwide, can facilitate communication between health professionals and the general population, and have been shown to be helpful in the prevention of T2D. Universal screening is needed. Noninvasive risk scores should be used in all countries, but they should be locally validated in all ethnic populations focusing on cultural differences around the world. Lifestyle interventions reduce the progression to prediabetes and diabetes. Nevertheless, many questions still need to be answered.